2006
DOI: 10.1177/0363546505282620
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Autograft Transplantation for Osteochondritis Dissecans of the Elbow in Juvenile Baseball Players

Abstract: Osteochondral autograft transplantation is a useful treatment for reattachment of the lesion as well as osteochondral resurfacing of elbow osteochondritis dissecans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 32 publications
1
149
0
2
Order By: Relevance
“…In general, early-stage OCD or stable lesion on the joint can be managed non-operatively with good outcomes [5,11]. In contrast, advanced OCD or unstable lesions generally require surgical management [10,29]. A variety of surgical techniques for OCD have been reported in the literatures with satisfied outcomes, such as debridement, drilling, fragment removal, fragment fixation, and autologous osteochondral mosaicplasty [16,26,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, early-stage OCD or stable lesion on the joint can be managed non-operatively with good outcomes [5,11]. In contrast, advanced OCD or unstable lesions generally require surgical management [10,29]. A variety of surgical techniques for OCD have been reported in the literatures with satisfied outcomes, such as debridement, drilling, fragment removal, fragment fixation, and autologous osteochondral mosaicplasty [16,26,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is indicated for patients who fail non-operative treatment and those with unstable lesions [6]. The surgical treatments are variable, including debridement, drilling or micro-fracture, fragment fixation, and osteochondral autograft transplantation [1,[7][8][9][10]. Among them, the debridement with fragment fixation is a time-tested procedure and one of the most widely used methods for surgical treatment of unstable capitellum OCD [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several authors have reported successful results after autologous osteochondral grafts for capitellar osteochondritis dissecans lesions (see Appendix) [10][11][12][13][14] . However, regarding sample size and follow-up interval, only one study, by Yamamoto et al 14 , is comparable with ours.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…However, regarding sample size and follow-up interval, only one study, by Yamamoto et al 14 , is comparable with ours. They described osteochondral autograft transplantation for capitellar osteochondritis dissecans in eighteen juvenile baseball players who had a good outcome after a minimum of twenty-four months (mean, forty-five months) 14 . We previously reported that seven of eight patients in the current series had excellent or good clinical results according to the clinical rating system of Timmerman and Andrews 18 at a minimum of fourteen months (mean, twenty-four months) 11 .…”
Section: Radiographic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation